High society : the central role of mind-altering drugs in history, science and culture - Jay, Mike, 1959 Dec. 14- (Rochester, Vt. : Park Street Press, 2010)
'An illustrated cultural history of drug use from its roots in animal intoxication to its future in designer neurochemicals'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Psychotropic drugs -- History; Drugs of abuse -- History; Psychopharmacology; Narcotics -- History